Sarcopenia and its impact on health: do they have significant associations? - Kamaruddin, Norshafarina Shair; Mohamed Sakian, Noor Ibrahim; Shahar, Suzana; Mohamad Hasnan, A.; Abdul Manaf, Zahara; Yassin, Zaitun (Penerbit Universiti Kebangsaan Malaysia, 2013)
A cross sectional study was conducted to determine the prevalence of Sarcopenia and its association with health profiles and oxidative stress among multiethnic older adults in an urban area of Malaysia. Sarcopenia was assessed using Bioimpedance analysis (BIA) and the associations between demography, socioeconomic status, lifestyle practices, health risk factors and blood profile were examined on 388 apparently healthy subjects aged 60 years and above. Prevalence of sarcopenia was 89.0% in men and 40.3% in women with the overall prevalence of 59.8%. It was found that prevalence of severe sarcopenia was 13.9% and sarcopenia obese was 23.5%. Binary logistic regression showed that there was no predictor found in men or women. However, a decline in muscle mass was observed in sarcopenic as compared with normal subjects. Sarcopenia is prevalent and there is a need to implement interventional strategies to prevent sarcopenia and its associated comorbidities.